BEAT 3.0 – a Tool for Integrated Biodiversity Assessments. Issue 1 (2nd August 2018) - Nygård, Henrik; Murray, Ciarán; Andersen, Jesper H.; Martin, Georg; Torn, Kaire; Korpinen, Samuli
BEAT 3.0 is a multi-metric indicator-based tool for integrated assessments of marine biodiversity status implemented in R. It follows the structure and requirements of the EU Marine Strategy Framework Directive and allows for use of monotonic, unimodal, conditional, trend-based and qualitative indicators. The tool handles tabular data files (.txt format), in which the assessment structure and indicator results are specified. Integration of indicators is primarily based on weighted averaging, where both spatial assessment scale and ecosystem level are considered. Parallel to the biodiversity status assessment, a confidence assessment is also included. BEAT 3.0 uses HELCOM Assessment units and HELCOM core indicators as default but can be customized for use in any geographical region and any set of indicators.